9514 1404 393
Answer:
(6.2, 4.5)
Step-by-step explanation:
We want, for some point P, ...
(P -A) / (B -P) = 1 / 3
3(P -A) = (B - P) . . . . . multiply by 3
4P = B +3A . . . . . . . . add P+3A
P = (B +3A)/4 . . . . . . .divide by 4
Filling in the coordinate values, we can find P to be ...
P = ((2.3, 5.4) +3(7.5, 4.2))/4 = (2.3+22.5, 5.4+12.6)/4
P = (6.2, 4.5)
Answer:
20 yd^2
Step-by-step explanation:
Your work is partially correct.
Assuming that the sides marked 8 yds and 2 yds are parallel, then the area of the trapezoid is
A = ( 8 yds + 2 yds)
------------------------ * 4 = 20 yd^2
2
Answer:
10
Step-by-step explanation:
There are 7 primes between 10 and 35: 11, 13, 17, 19, 23, 29, 31.
The product of 11 and any of the others will be less than 350, 6 products.
The product of 13 and any below 26 will be less than 350, 3 more products.
The product of 17 and any below 20 will be less than 350, 1 more product.
There are a total of 10 different products below 350 possible.
_____
11·13, 11·17, 11·19, 11·23, 11·29, 11·31, 13·17, 13·19, 13·23, 17·19
The equation seems to be
1
-------- = 5 ^ (x + 4)
25
In that case, this is the solution, stept by step:
1) factor 25: 25 = 5^2
1
=> ----------- = 5^(x + 4)
5^2
2) invert 5^2
=> 5^(-2) = 5^(x+4)
3) Given that the bases are equal, the exponents also have to be equal:
=> - 2 = x + 4
3) transpose +4:
=> - 2 - 4 = x
=> x = - 6
Answer: - 6
Answer:
Step-by-step explanation:
Combine like terms. Like terms have same variable with same power
a) (2xy + 4x) + (15xy - 5x) = <u>2xy + 15xy</u> +<u> 4x - 5x</u>
= 17xy - x
b) (6a + 4b² - 3) + (3b² - 5) = 6a + <u>4b² + 3b²</u> <u>- 3 - 5 </u>
= 6a + 7b² - 8
c) (4x³ - 3x² +4x) + (8x² - 5x ) = 4x³ <u>- 3x² + 8x²</u> <u>+ 4x - 5x</u>
= 4x³ + 5x² - x
d) (7b - 6a + 9y) - (12b + 5a - 2y) =
In subtraction, add the additive inverse of (12b + 5a - 2y)
additive inverse = - 12b - 5a + 2y
(7b - 6a + 9y) - (12b + 5a - 2y) = 7b - 6a + 9y -12b -5a + 2y
= 7b - 12b -6a - 5a + 9y + 2y
= -5b - 11a + 11y
e) (2x² + 7x - 2 + 9y) - (13x + 4x² + 5 - 6y)
Additive inverse of 13x + 4x² + 5 - 6y = -13x + 4x² - 5 + 6y
(2x² + 7x - 2 + 9y) - (13x + 4x² + 5 - 6y)= 2x² + 7x - 2 + 9y -13x - 4x² -5 +6y
= 2x² - 4x² + 7x -13x -2 - 5 + 9y + 6y
= -2x² - 6x - 7 + 15y